2023
DOI: 10.3390/cells12172160
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties and Cellular Metabolic Characteristics of 3D Spheroids Are Possible Definitive Indices for the Biological Nature of Cancer-Associated Fibroblasts

Nami Nishikiori,
Kohichi Takada,
Tatsuya Sato
et al.

Abstract: The current study’s objective was to elucidate some currently unknown biological indicators to evaluate the biological nature of cancer-associated fibroblasts (CAFs). For this purpose, four different CAFs, CAFS1, CAFS2, SCC17F and MO-1000, were established using surgical specimens from oral squamous cell carcinomas (OSCC) with different clinical malignant stages (CAFS1 and CAFS2, T2N0M0, stage II; SCC17F and MO-1000, T4aN2bM0, stage IVA). Fibroblasts unrelated to cancer (non-CAFs) were also prepared and used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
(88 reference statements)
0
1
0
Order By: Relevance
“…Apart from the immune system, mounting evidence revealed that the TME accelerates cell proliferation, metastatic activities, and chemoresistance in pancreatic cancer. 37 , 38 Gap junction beta‐4 could also affect the metastatic potential and functions of pancreatic cancer TME. Unfortunately, we could not evaluate whether GJB4 increased metastases and influenced the TME because it was neither a model of metastases nor of allogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the immune system, mounting evidence revealed that the TME accelerates cell proliferation, metastatic activities, and chemoresistance in pancreatic cancer. 37 , 38 Gap junction beta‐4 could also affect the metastatic potential and functions of pancreatic cancer TME. Unfortunately, we could not evaluate whether GJB4 increased metastases and influenced the TME because it was neither a model of metastases nor of allogeneity.…”
Section: Discussionmentioning
confidence: 99%